The profile of health - oral disease and treatment of urban Lima 2012 seniors needs - Campodónico Reátegui, Carlos (2013)
The main objective of this study was to determine the profile of oral health and disease of the elderly adults of urban Lima, taking into account the prevalence of dental caries, periodontal disease, oral mucosa injuries and treatment needs. Descriptive and transversal study was using over 120 elderly adults (over 60 years old), living in Lima center and district. Data collection was performed by the method of clinical observation and interview using rates and procedures of the WHO. The results obtained were: average age 71 years, high prevalence of the female gender (70%) and secondary education, presence of hypertension with 33 % and diabetes mellitus with 10.8%, the mucosal disorders in 10.8 %, with ulceration type localized on the palate and alveolar ridges. Also was observed presence of calculi and periodontal bleeding in 52% of the population. The study subjects requiring prophylaxis in 23.3 % and needed just a case of root planing in 11%. Teeth present in the mouth, the 23% have lost fixation at 4-5 mm. Only 5.82 % of the teeth are healthy, with an average of 4.43 cavities, missing teeth 14.77 with 53%. The DMF had a mean of 19.71 with a Ds . 6.74. The 31.7 % use removable full dentures and fixed prostheses by 19.2 %. In the lower jaw using PPR with 20% and 13.3 % use full dentures and fixed prostheses with 9.27%. Finding a high need for the use of removable dentures in upper and lower jaw. It was determined that the oral health of older people is poor due to the poor hygiene, introduction of caries and periodontal disease and in dire need of restoration of cavities, use of removable, removable total and fixed partial denture.